29. CURRENT SITUATION OF KNOWLEDGE ABOUT PREVENTING INJURIES OF THE PEOPLE IN 2 COMMUNES OF VU THU DISTRICT, THAI BINH PROVINCE, IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the current status of knowledge regarding injury prevention among residents in two communes of Vu Thu district, Thai Binh province, in 2024.Subjects and methods: The study was conducted on 411 people in Minh Khai and Song Lang communes, Vu Thu district, Thai Binh province. Using a pre-designed questionnaire, the subjects were interviewed directly. The assessment of people’s knowledge of accident and injury prevention was determined by each question, with the threshold being 70% or more of the total number of responses.Results: Surveying 411 people showed that the knowledge of prevention of injury accidents was limited. Only 27.3% of people have knowledge about types of accidents; 67.4% of people have knowledge about the impact of injury accidents. Knowledge of prevention of injury accidents in labor and transportation respectively 83.9% and 79.3% respectively; meanwhile, in daily activities and for children under 5 years old only 28.5% and 28.2%. The more related analysis shows that the higher the education level, the more complete knowledge about injury accidents, with OR ranges from 1,611 to 5,168.Conclusion: People lack comprehensive knowledge about injury prevention, especially in daily life and with children. The results emphasized the role of education in raising awareness and skills to prevent injury in the community.
Keywords: Injury; knowledge; prevention; Thai Binh.